Echoes of “Holland revolution” in the contemporaneity: cultural practices, ethics and social commitment (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
This paper analyzes the ethical and the technological dimensions of the Behavioral Analysis of Culture. More precisely, the analysis takes as starting point the seminal publication by J. G. Holland, in which he inquires about whether the behavioral principles would be of any value to revolutionary demonstrations, examines the aspects that are closely related to an individual’s academic background and personal his-tory of interactions, and to the rational justification of values, all of which constitute crucial conditions in establishing the purposes of cultural designs. Considering that social transformation is inseparable from cultural planning, this paper discusses alternatives to the involvement of behavior analysts in projects that contribute to social justice consolidation.
Keywords: behavioral revolution; cultural practices; ethics and behaviorism; behavioral analysis of culture; radical behaviorism